Protective Effect of Oral BCG and Inactivated Mycobacterium bovis Vaccines in European Badgers (Meles meles) Experimentally Infected With M. bovis - Balseiro, Ana; Prieto, José Miguel; Álvarez, Vega; Lesellier, Sandrine; Davé, Dipesh; Salguero, Francisco J.; Sevilla, Iker A.; Infantes-Lorenzo, José Antonio; Garrido, Joseba M.; Adriaensen, Hans; Juste, Ramón A.; Barral, Marta (Frontiers in Veterinary Science, 2020)
In Europe, badgers (Meles meles) are recognized as major tuberculosis (TB) reservoir hosts with the potential to transmit infection to associated cattle herds. Recent studies in Spain have demonstrated that vaccination with a heat-inactivated Mycobacterium bovis vaccine (HIMB) successfully protects captive wild boar and red deer against progressive disease. The aim of this study was to evaluate the efficacy of two oral vaccines against TB in a badger model: the live-attenuated M. bovis bacillus Calmette-Guérin BCG vaccine (Danish strain) and a HIMB vaccine. Twenty-four badgers were separated in three treatment groups: oral vaccinated with live BCG (108 CFU, n = 5), oral vaccinated with HIMB (107 CFU, n = 7), and unvaccinated controls (n = 12). All badgers were experimentally infected with M. bovis (103 CFU) by the endobronchial route targeting the right middle lung lobe. Throughout the study, clinical, immunological, pathological, and bacteriological parameters of infection were measured. Both vaccines conferred protection against experimental TB in badger, as measured by a reduction of the severity and lesion volumes. Based on these data, HIMB vaccination appears to be a promising TB oral vaccine candidate for badgers in endemic countries.